Diversity of D-Amino Acid Utilizing Bacteria From Kongsfjorden, Arctic and the Metabolic Pathways for Seven D-Amino Acids - Yu, Yang; Yang, Jie; Zheng, Li-Yuan; Sheng, Qi; Li, Chun-Yang; Wang, Min; Zhang, Xi-Ying; McMinn, Andrew; Zhang, Yu-Zhong; Song, Xiao-Yan; Chen, Xiu-Lan (Frontiers in Microbiology, 2020)
D-amino acids (DAAs) are an important component of the refractory dissolved organic matter pool in the ocean. Microbes play a vital role in promoting the recycling of DAAs in the ocean. However, the diversity of marine DAA-utilizing bacteria and how they metabolize DAAs are seldom studied. Here, by enrichment culture with DAAs as the sole nitrogen source, bacteria of 12 families from three phyla were recovered from surface seawater and sediment from Kongsfjorden, Arctic, and seven DAA-utilizing bacterial strains were isolated. These strains have different DAA-utilizing abilities. Of the seven DAAs used, Halomonas titanicae SM1922 and Pseudoalteromonas neustonica SM1927 were able to utilize seven and five of them, respectively, while the other strains were able to utilize only one or two. Based on genomic, and transcriptional and biochemical analyses, the key genes involved in DAA metabolism in each strain were identified and the metabolic pathways for the seven DAAs in these marine bacteria were identified. Conversion of DAAs into α-keto acids is generally the main pathway in marine DAA-utilizing bacteria, which is performed by several key enzymes, including DAA oxidases/dehydrogenasesoxidoreductases/dehydrogenases, D-serine ammonia-lyases, D-serine ammonia-lyase DSD1s and DAA transaminases. In addition, conversion of DAAs into LAAs is another pathway, which is performed by amino acid racemases. Among the identified key enzymes, D-serine ammonia-lyase DSD1 and Asp racemase are first found to be employed by bacteria for DAA utilization. These results shed light on marine DAA-utilizing bacteria and the involved DAA metabolism pathways, offering a better understanding of the DAA recycling in the ocean.